Effect Of Combined Therapy Of Intravenous Ceftriaxone And Oral Polyherbal Drug On Milk Enzyme Activity In Healthy And Mastitic Goats (Applied Biological Research, 2012)
Fibrosin®, a poyherbal drug, helps in cleansing udder tissue and let down  of milk. The present study was aimed to evaluate milk enzyme activities in mastitic goats following single dose intravenous administration of  ceftriaxone, with 1 h pre-single dose oral administration of polyherbal  drug. Eighteen clinically healthy lactating black Bengal goats were  divided into 3 groups (group I, II and III). Mastitis was artificially induced by inoculating 35,000 cfu of coagulase positive Staphylococci intracisternally to the right teat of group-III goats. Diagnosis of mastitis  was confirmed by bromothymol blue paper test and manifestation of  clinical signs. A single intravenous dose of ceftriaxone was administered  at 50 mg kg-1 body weight to each goat of group-I while a half bolus of  polyherbal drug (1.9 g) was administered orally to each goat in group-II  and III before 1 h of ceftriaxone administration. The milk alkaline  phosphatase and catalase activities significantly increased in mastitic  goats as compared to the healthy ones. Mean reduced glutathione level in  milk of mastitic goats was increased while milk lactoperoxidase activity  showed a decreased activity. The intravenous administration of  ceftriaxone with 1 h pre-single dose oral administration of polyherbal  drug inmastitic goats resultedindecreasein milk alkaline phosphatase and catalase activities; and also reduced glutathione to normal level while lacto peroxidase activity, a natural antimicrobial system of milk, significantly  increased in mastitic goats. The polyherbal drug Fibrosin® may be a  better supportive therapy with intravenous cetriaxone to treat mastitis.
Keywords: Ceftriaxone; fibrosin; mastitis; milk enzyme; polyherbal drug